An impact behavior analysis of CNT‐based fiber reinforced composites validated by LS‐DYNA: A review. Issue 1 (13th May 2015) - Rawat, Prashant; Singh, Kalyan Kumar
Abstract : In last 2 decades use of CNT based‐Fiber Reinforced Polymer (FRP) Composite have revolutionized the aerospace, automobile, marine industry as it have showed exceptional mechanical properties like impact resistant, high energy absorbing capacities, damping properties, etc. The goal of this review is to explore the validation of impact behavior in CNT based FRP composite by LS‐DYNA. Impact behavior depends upon various parameters like velocity of impact, shape of impactor and its weight, environmental conditions as temperature dependency, contact time and damage area and many other considerations. Prediction of impact damage is done using methods like absorbed energy, gross damage produced and/or micro energy dissipation. This article also presents study of variation in impact behavior by varying CNT percentage in composite laminates. POLYM. COMPOS., 38:175–184, 2017. © 2015 Society of Plastics Engineers